Linguistic Typology (De Gruyter Mouton, 1997)
Linguistic Typology publishes research on linguistic diversity and unity. It welcomes articles that report empirical findings about crosslinguistic variation, advance our understanding of the patterns of diversity, or refine typological methodology.